Penerapan Augmented Reality Pada Media Promosi Pariwisata (Studi Kasus: New Small World) - Aldika Muliyansyah (E-Jurnal Universitas Samudra, 2022)
Abstract Promotion is a way of marketing that is done to provide information about a product and in its use promotional media is usually used to attract someone's interest in goods, services or something offered by the maker of the promotion. The purpose of this study is to increase the interest of potential visitors by innovating the promotional media used, applying Augmented Reality technology as the development of existing media, which is a new innovation in the New Small World promotional media. The result of this research is the AR New Small World application where from the brochure, miniature animated 3D objects can be displayed and also contain information on each object through a smartphone that can make the media interactive and informative. Keywords: Promotional Media, New Small World, Augmented Reality, MDLC, Brochure.